PENGARUH VARIASI PARAMETER PENGELASAN TERHADAP KEKUATAN SAMBUNGAN HASIL FRICTION WELDING PADA BAJA ST.41 - Picki Ilham; Rodika Rodika; Somawardi Somawardi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Friction welding is a type of welding that connects two materials with the heat generated by the material itself so that it does not require additional materials. Heat can occur due to the presence of two objects rubbing against each other so that the material can melt and there is a connection due to forging process. The purpose of this study was to determine the impact strength of friction welding joints. The material used in this research is low carbon steel St.41 in the form of of a solid cylinder which has a diameter of 13mm. From the research that has been done, it is found that friction welding using 720 and 1000 rpm have better joint strength than using 450 rpm, which means that specimens with 720 and 1000 rpm have a higher amount of energy absorbed and impact values than specimens using 450 rpm.